Could dysnatremias play a role as independent factors to predict mortality in surgical critically ill patients?. Issue 9 (March 2017) - Nicolini, Edson A.; Nunes, Roosevelt S.; Santos, Gabriela V.; da Silva, Silvana Lia; Carreira, Mariana M.; Pellison, Fernanda G.; Menegueti, Mayra G.; Auxiliadora-Martins, Maria; Bellissimo-Rodrigues, Fernando; Feres, Marcus A.; Basile-Filho, Anibal
Abstract : Abstract: Several studies have demonstrated the impact of dysnatremias on mortality of intensive care unit (ICU) patients. The objective of this study was to assess whether dysnatremia is an independent factor to predict mortality in surgical critically ill patients admitted to ICU in postoperative phase. One thousand five hundred and ninety-nine surgical patients (58.8% males; mean age of 60.6 ± 14.4 years) admitted to the ICU in the postoperative period were retrospectively studied. The patients were classified according to their serum sodium levels (mmol/L) at admission as normonatremia (135–145), hyponatremia (<135), and hypernatremia (>145). APACHE II, SAPS III, and SOFA were recorded. The capability of each index to predict mortality of ICU and hospital mortality of patients was analyzed by multiple logistic regression. Hyponatremia did not have an influence on mortality in the ICU with a relative risk (RR) = 0.95 (0.43–2.05) and hospital mortality of RR = 1.40 (0.75–2.59). However, this association was greater in patients with hypernatremia mortality in the ICU (RR = 3.33 [95% confidence interval, CI 1.58–7.0]) and also in hospital mortality (RR = 2.9 [ 95% CI = 1.51–5.55). The pairwise comparison of ROC curves among the different prognostic indexes (APACHE II, SAPS III, SOFA) did not show statistical significance. The comparison of these indexes with serum sodium levels for general population, hyponatremia, and normonatremia was statistically significant ( P  < .001). For hypernatremia, the AUC and 95% CI for APACHE II, SAPS III, SOFA, and serum sodium level were 0.815 (0.713–0.892), 0.805 (0.702–0.885), 0.885 (0.794–0.945), and 0.663 (0.549–0.764), respectively. The comparison among the prognostic indexes was not statistically significant. Only SOFA score had a statistic difference compared with hypernatremia ( P  < .02). The serum sodium levels at admission, especially hypernatremia, may be used as an independent predictor of outcome in the surgical critically ill patients.